1992
DOI: 10.1159/000111654
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendrocytes from Jimpy and Normal Mature Tissue Can Be 'Activated' when Transplanted in a Newborn Environment

Abstract: Fragments of corpus callosum from P13 normal and jimpy (jp) mutant mice (containing only postmigrating precursors and differentiated oligodendrocytes (ODCs, some of them myelinating soon) have been transplanted into the thalamus of newborn shiverer (shi) mutant mice. The behaviour of transplanted ODCs has been assayed by immunohistochemistry of their myelin basic protein (MBP)-positive myelin synthesized in the host shi brain whose myelin is deprived of this component. ODCs and postmigrating precursors contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…However, it was later shown that adult murine oligodendrocytes can proliferate in response to trauma (Ludwin, 1984). In a more recent work, it has been demonstrated that in a transplantation setting oligodendrocytes (or their precursors) from a mature host can migrate to some extent and even contribute to myelination (Lachapelle et al, 1992). Hence, it is quite conceivable that host oligodendrocytes or resting oligodendrocyte precursors are activated by the embryonic graft tissue to invade the graft and contribute to graft myelination.…”
Section: Fig 5 Immunocytochemical Localization Of Amog432 Expressionmentioning
confidence: 99%
“…However, it was later shown that adult murine oligodendrocytes can proliferate in response to trauma (Ludwin, 1984). In a more recent work, it has been demonstrated that in a transplantation setting oligodendrocytes (or their precursors) from a mature host can migrate to some extent and even contribute to myelination (Lachapelle et al, 1992). Hence, it is quite conceivable that host oligodendrocytes or resting oligodendrocyte precursors are activated by the embryonic graft tissue to invade the graft and contribute to graft myelination.…”
Section: Fig 5 Immunocytochemical Localization Of Amog432 Expressionmentioning
confidence: 99%
“…The ability of transplanted glial cells to ensheath axons and synthesize myelin when transplanted into dysmyelinating mutants or chemically created models of demyelination has been studied extensively (1)(2)(3)(4)(5)(6). Until now the primary assay of myelin-forming grafts has of necessity been anatomical rather than functional or electrophysiological.…”
mentioning
confidence: 99%
“…Apoptotic death is the fate of all growth factor-deprived immature oligodendrocytes (Barres et al, 1992) , raising the question of whether PLP is involved in a cell-specific survival mechanism. Moreover, after transplantation of jimpy cells into normal brains (shiverer is used for technical reasons), some oligodendrocytes survive for a very long time (Lachapelle et al, 1992). Both survival and differentiation of cultured jimpy oligodendrocytes can be improved by an astrocyte-condition medium (Bartlett et al, 1988).…”
mentioning
confidence: 99%